Identification of Bisphenol-A (BPA) in Polycarbonate (PC) Baby Bottles in Jayapura, Papua - Barus, Andre Anusta; Appa, Felycitae Ekalaya; Bakri, Nur Fadilah; Pratiwi, Mustika Endah; Tobi, Claudius Hendraman B. (STMIK Widya Cipta Dharma, 2025)
Bisphenol-A (BPA) is found in various types of food packaging, such as plastic bottles, paper-based packaging, and the inner lining of canned foods. BPA is widely used in the production of polycarbonate (PC) plastics due to its strength and heat resistance. However, BPA can migrate into food or beverages through physical mechanisms, resulting from the diffusion of loosely bound BPA within the polymer matrix, or through chemical mechanisms triggered by hydrolysis reactions at high temperatures or extreme pH conditions. This study aims to evaluate the migration levels of BPA from polycarbonate (PC) packaging into water at various temperatures using UV-Vis spectrophotometry. The experiment was conducted by adding water into polycarbonate baby bottles at temperatures of 60–100°C, allowing it to sit for 30 minutes before analysis. The test results were compared with the safe BPA consumption limit set by the European Food Safety Authority (EFSA), which is 4 µg/kg body weight per day, as well as the BPOM standard, which establishes a BPA migration limit of 0.6 mg/kg per day. The results showed that BPA was not detected in water that had been in contact with polycarbonate baby bottles at the tested temperatures. Absorbance measurements indicated negative values, suggesting that the detected BPA levels were below the method's detection limit. This indicates that BPA migration is extremely low or undetectable, suggesting that its use under normal conditions can be considered safe.